Arginine catabolism by Treponema denticola. - Blakemore, R P (1976)
Treponema denticola, an anaerobe commonly present in the human mouth, ferments various amino acids and glucose. Amino acid analyses indicated that substrate amounts of arginine were utilized by T. denticola growing in a complex, serum-containing medium. Cell suspensions metabolized L-arginine to citrulline, NH3, CO2, proline, and small amounts of ornithine. CO2, NH3, ornithine, and proline were produced from L-citrulline by cell suspensions. Determinations of radioactivity in products formed from L-[U-14C]ornithine indicated that cell suspensions converted this amino acid to proline. Furthermore, proline was excreted by cells growing in a complex, arginine-containing medium. Arginine iminohydrolase (deiminase) and ornithine carbamoyltransferase activities were detected in T. denticola cell extracts. Carbamoylphosphate dissimilation by extracts yielded adenosine triphosphate. The data indicate that T. denticola derives energy by dissimilating L-argine via the arginine iminohydrolase pathway. However, unlike some of the other bacteria that utilize this pathway, T. denticola converts to proline much of the ornithine derived from L-arginine.